2004
DOI: 10.1080/13547500410001728390
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oxidative DNA damage in lymphocytes of patients with Alzheimer's disease

Abstract: Oxidative damage to DNA may play an important role in both normal ageing and in neurodegenerative diseases. The deleterious consequences of excessive oxidations and the pathophysiological role of reactive oxygen species have been intensively studied in Alzheimer's disease. Although the role of oxidative stress in the aetiology of Alzheimer's disease is still not clear, the detection of an increased damage status in the cells of patients could have important therapeutic implications. The levels of oxidative dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 21 publications
(21 reference statements)
7
43
0
4
Order By: Relevance
“…Higher concentrations of oxidized pyridines and purines were detected in lymphocytes and leukocytes of AD patients compared with controls [6,[112][113][114], and increased levels of 8-oxoG were observed in DNA from ventricular CSF of AD patients [115]. Recent findings indicate increased oxidative damage in leukocytes [6] and brain tissue [17] of subjects with MCI, which suggests that DNA oxidation may constitute an early event in the progression of AD, before cytopathological alterations, and may contribute to the pathogenesis of the disease.…”
Section: Dna Oxidation and Accumulation In Alzheimer Diseasementioning
confidence: 99%
“…Higher concentrations of oxidized pyridines and purines were detected in lymphocytes and leukocytes of AD patients compared with controls [6,[112][113][114], and increased levels of 8-oxoG were observed in DNA from ventricular CSF of AD patients [115]. Recent findings indicate increased oxidative damage in leukocytes [6] and brain tissue [17] of subjects with MCI, which suggests that DNA oxidation may constitute an early event in the progression of AD, before cytopathological alterations, and may contribute to the pathogenesis of the disease.…”
Section: Dna Oxidation and Accumulation In Alzheimer Diseasementioning
confidence: 99%
“…Oxidative stress represents the loss of balance between the processes of the creation of free radicals and those that are responsible for the removal of oxidized macromolecules (antioxidative cascade) which again leads to cellular dysfunction (changes in cellular homeostasis) and results in increased genomic instability and eventually in cell death (25). Most likely, the oxidative stress is the essence of a greater DNA damage compared to adequate control (18,26,27) as one of the initial factors that lead to further genomic instability (28)(29)(30). There is substantial evidence supporting the fact that genetic instability is increased in AD lymphocytes compared to corresponding controls.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Studies related to the role of oxidative stress in neurodegenerative diseases are limited with patients with AD and several studies demonstrated elevated levels of oxidative DNA damage and an impairment in the removal of oxidized purines in the lymphocytes of patients with AD. [16][17][18][19] A significant increase of 8OHG and an oxidized amino acid (nitrotyrosine) were detected in neurons of patients with AD suggesting that increased oxidative damage is an early event in AD that decreases with the progression of the disease. 40 The level of oxidative damage and repair capacity in peripheral lymphocytes of AD patients and their age-matched controls was determined by the comet assay applied to freshly isolated blood samples with oxidative lesion-specific DNA repair endonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] A significantly higher levels of basal and oxidative DNA damage were found in the lymphocytes as well as in the polymorphonuclear leukocytes of patients with AD and with mild cognitive impairment (MCI). [17][18][19] Studies in patients with AD showed increased levels of 8-hydroxyguanosine (8OHG) or 8-hydroxy-2'-deoxyguanosine (8OHdG) in addition to decreased levels of plasma antioxidants as compared to controls. 5,11,17,[20][21][22][23] On the other hand, most studies on patients with AD have been performed in post-mortem tissues with advanced disease without clarifying whether oxidative stress is an early event or a common final step secondary to the degenerative process.…”
mentioning
confidence: 99%
See 1 more Smart Citation